Pengaruh Motivasi Dan Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Gatama Prima Jasa - Doni Romdoni; Yoewono; Yanna Puspasari (JURNAL ILMU ADMINISTRASI PUBLIK DAN BISNIS, 2020)
This research aims to find out the influence of motivation and leadership on the performance of PT employees. Gatama Prima Jasa. The data source in the author's study was taken from primary data and some secondary data, taken directly in the field by disseminating research instruments in the form of questionnaire statements. The resulting data is in the form of ordinal using a Likert scale, which is 1 to 5. Sample withdrawal uses the slovin formula with an error rate of 10%. The sample was sampled by 64 people from a population of 175 people. Data analysis techniques using Multiple Linear Regression Analysis. The results of the study were partially 47.6% percent of r2=0.476 Real motivation to influence and improve the performance of PT employees. Gatama Prima Jasa. Partially 33.4% percent of r2=0.344 Real leadership affects and improves PT Employee Performance. Gatama Prima Jasa. Together the influence of Motivation and Leadership variables on Performance variables is 50.6% percent of the value r2=0.506 and the remaining 49.4% percent is influenced by other factors such as ability and expertise, background, demographics, perception, attitude, personality, learning, resources, awards, structure, job design and others.